ECCENTRIC KNEE FLEXOR STRENGTH AND HAMSTRING INJURY RISK IN ATHLETES WITH HISTORY OF ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION. Issue 4 (1st February 2017) - Messer, Daniel; Bourne, Matthew; Timmins, Ryan; Opar, David; Williams, Morgan; Shield, Anthony
Abstract : Background: Hamstring strain injuries (HSIs) are the most common cause of time loss from training and competition in elite football. Anterior cruciate ligament (ACL) ruptures are also prevalent and typically require surgery from hamstring grafts, which often results in chronic deficits in eccentric knee flexor strength, a known risk factor for HSI. Objective: We aimed to determine the effect of prior ACL reconstruction (ACLR) on 1) eccentric knee flexor strength during the Nordic hamstring exercise (NHE) and; 2) the risk of future HSI. We hypothesised that athletes with a prior ACLR would display 1) lower levels of eccentric knee flexor strength than athletes without such history and; 2) an increased risk of future HSI. Design: Prospective study. Setting: Secondary analysis of 3 studies previously completed in Australian sport. Patients (or Participants): 541 elite to sub-elite male footballers had their eccentric knee flexor strength assessed using the NHE. Reports of HSIs and any history of ACL injuries were obtained. All participants were categorized into injury history groups. Interventions (or Assessment of Risk Factors): Injury history, eccentric strength. Main Outcome Measurements: Prospective HSI occurrence. Results: Athletes with history of ACLR were 39N (95% CI, 14.2–67.1; P<0.005) weaker in the injured limb compared to the contralateral limb. Athletes with history of ACLR had a 3.18-fold (95% CI, 1.9–5.2; P<0.001) greater risk of subsequent HSI than athletes without such history and was augmented to 5.69 (95% CI, 3.2–9.5; P<0.001) if they had suffered HSI in the previous 12 months. Conclusions: ACLR injured limbs are significantly weaker than uninjured limbs. Athletes with prior ACLR are significantly more likely to suffer future HSI, particularly if they have a recent history of HSI. This is the first adequately powered study to have assessed the effect of prior ACLR on future HSI risk.